Advances in Pacific Basin business, economics and finance. - Lee, Cheng F.; Yu, Min-Teh (Advances in Pacific Basin business, economics and finance,, 2018)
Advances in Pacific Basin Business, Economics, and Finance is an annual publication designed to focus on interdisciplinary research in finance, economics, and management among Pacific Rim countries. All articles published are reviewed and recommended by at least two members of editorial board. Topics of interest include, but are not limited to, the following;1. Policy and management on financial markets and financial institutions; 2. Options, futures and other derivatives markets; 3. Corporate finance and investment decisions; 4. Insurance and risk management; 5. Accounting, auditing and taxation; 6. Marketing, management, and business policies of the Pacific Rim countries; 7. Interdisciplinary issues on supply chain, finance, and marketing; 8. Monetary and foreign exchange policy; 9. Income, employment and other economic policies among the Pacific Rim countries.